Multichannel reflection seismic data from the Campi Flegrei caldera (Italy): profiles GeoB08-032,GeoB08-050,GeoB08-065, GeoB08-070 - Steinmann, Lena; Spieß, Volkhard; Sacchi, Marco (PANGAEA, 2020)
To date, the origin of the Campi Flegrei caldera is still under debate and may be related to (1) a single caldera collapse associated with the Neapolitan Yellow Tuff (NYT) eruption, (2) two subsequent caldera collapses associated with the NYT and the preceding Campanian Ignimbrite (CI) eruptions forming a nested-caldera complex, or (3) not related to a caldera collapse after all. Here, we study the submerged portion of the caldera, which has favored a marine depositional setting and, thus, represents an ideal location for the reconstruction of its formation history, utilizing multichannel seismic data. Volcanic deposits and edifices were seismically distinguished from sedimentary successions, and the stratigraphy could be refined and extended back to the Campanian Ignimbrite eruption at ~39 ka. High-resolution multichannel reflection seismic data revealed the existence of a nested-caldera complex formed during the CI eruption at ~39 ka and the more recent NYT eruption at ~15 ka. A ring-fault bounding an inner caldera collapse structure was clearly imaged. It appears that this inner ring-fault was initially activated during the CI caldera collapse and later reactivated during the NYT caldera collapse with different amounts of subsidence. The NYT caldera probably formed during an asymmetrical collapse with a maximum subsidence of ~75 m in the offshore portion. The vertical displacement related to the CI caldera collapse may be significantly larger. The submerged caldera depression accommodates post-eruption sediments. Within this high-resolution archive, two major unconformities developed at ~8.6 ka and 5 ka, when resurgence-related uplift exceeded the rate of sea-level rise concurrent with the emersion of the La Starza terrace. A previously unknown post-collapse submarine volcanic mound located between Nisida Island and Nisida Bank probably formed between 4.8 and 3.7 ka. Also, the Penta Palummo Bank appears to be constructed of at least two monogenetic volcanic edifices, the Penta Palummo volcano formed at ~100 ka and a younger mushroom-shaped unit formed between 39 and 15 ka. The main outcome of this study is a conceptual evolutionary model, providing novel insights on the formation of the Campi Flegrei nested caldera in the course of two large-scale eruptions (CI and NYT) with associated caldera collapses along mutual (i.e. reactivated) faults and subsequent caldera resurgence. As both the genesis and subsurface architecture of the Campi Flegrei caldera are still hotly debated topics in literature, our discoveries can be regarded as a substantial advancement in the understanding of the Campi Flegrei volcanic area.
Keywords: caldera; Campi Flegrei; GI gun; multichannel reflection seismics; resurgence; ring fault